Breach of Contract in the Cooperative Management Agreement of Oil Palm Plantations: A Research Study in Suro Makmur, Aceh Singkil - Rahman Rahman; Sanusi Sanusi; M. Jafar (International Journal of Law and Society, 2026)
Cooperative agreements for the management of oil palm plantations constitute a common legal relationship among communities in Suro Makmur, Aceh Singkil. Under Indonesian civil law, agreements are governed by the Indonesian Civil Code, particularly Articles 1320 and 1338, which regulate the validity and binding force of contracts. Accordingly, each party is required to fulfill the rights and obligations agreed upon in the contract. In practice, however, oil palm plantation management agreements frequently result in breaches of contract due to the failure of one or more parties to perform their obligations. Such breaches may take the form of non-performance, delayed performance, improper performance, or actions contrary to contractual provisions, as regulated in Article 1234 of the Indonesian Civil Code. These violations often lead to economic losses, reduced trust between parties, and legal uncertainty. Furthermore, Articles 1238 and 1243 stipulate that parties committing a breach of contract may be liable for compensation, costs, and damages arising from non-performance. This study employed an empirical juridical method with a qualitative approach through interviews, field observations, and library research. The findings reveal that breaches commonly occur in the form of failure to fulfill obligations, delays, improper performance, and actions inconsistent with the agreement. Disputes are generally resolved through non-litigation mechanisms, such as deliberation and mediation involving customary leaders or village authorities, while court proceedings are pursued only when amicable settlement fails. The study concludes that legal certainty requires not only contractual agreements but also good faith and legal awareness among the parties. Therefore, comprehensive written agreements regulating rights, obligations, profit-sharing, duration, and dispute resolution mechanisms are essential to prevent breaches of contract and strengthen legal certainty.